Identification of best growth curve model for Anatolian black cattle - Sakar, Çagri Melikşah (Slovenian veterinary research, 2023)
The aim of this study was to identify the model that best describes the growth trajectory from birth to 24 months of age in Anatolian Black Cattle (ABC) raised for con-servation purposes. A total of 493 weight records of 113 animals at birth, 3, 6, 12, 18, and 24 months were collected. Six different non-linear models were used to describe the growth curve of animals: 2nd degree polynomial, 3rd degreee polynomial, Logistic, Brody, Von Bertalanffy, and Gompertz models. In the study, R2 values of the models were: 0.997, 0.999, 0.953, 0.979, 0.924, and 0.862; corel values (correlation between the observed and estimated curves) were 0.994, 0.998, 0.989, 0.993, 0.961, and 0.703; Residual Standard Deviations (RSD) were 3.216, 1.388, 11.533, 3.561, 14.736, and 27.141, respectively. Given these values, it was found that the 3rd degree polynomial model was the best to describe the growth curve of ABC. As a result of the analyses, it was noticed that the values predicted by this model deviated by 1-3 kg from the observed values in all periods and in all environmental factors examined (sex, dam age, parity, birth year and birth, season). It was found that these differences increased up to 4-5 kg only in the 18-month period. The results also showed that ABC continued to grow after 24 months of age. As a result, traits such as age at sexual maturity, breeding age, and slaughter age can be easily predicted by identifying the model that best describes growth and development in herds.
Keywords: Anatolian black cattle; anatolsko črno govedo; deslorelinski implantat; dolgo delujoči GnRH; growth curve; krivulja rasti, nelinearni modeli; live weight; non-linear models; živa teža